Additional electron transfer channels of thermostable 0D Cs(Pb: Pt)Br3 perovskite quantum dots /2D accordion-like Ni-MOF nanojunction for photocatalytic H2 evolution. (15th December 2022) - Zhang, Xian; He, Man; Fang, Hao; Bao, Jiehua; Bu, Xiaohai; Yang, Chenghan; Sheng, Xiaoli; Wu, Bo; Zhang, Zewu; Zhou, Yuming
Abstract: Overcoming the low charge transfer efficiency and poor photothermal stability of halide perovskite quantum dots (QDs) is the booster to achieve photocatalytic applications. In this paper, the Pt 2+ -doped CsPbBr3 QDs/two-dimensional accordion-like Ni-MOF (CPPB QDs/Ni-MOF) composite was firstly synthesized by fixing the CPPB QDs into the pores of Ni-MOF. Electron separation and transfer efficiency were analyzed by PL spectra and electrochemical data. The photocatalyst exhibited outstanding photocatalytic performance in hydrogen (H2 ) evolution. The optimal H2 evolution efficiency of the composite reached 153.6 μmol h −1, which was about 9 times than that of pure Ni-MOF and remained 134.8 μmol h −1 after the cycle test. The splendid efficiency could be benefited from the advantages of 2D layered structure of Ni-MOF and the high charge separation and transmission efficiency of CPPB QDs. Finally, the mechanism of electron migration and additional electron transfer channels between composite interfaces was further demonstrated by density functional theory (DFT) calculations. The present work opens up a novel perspective for photocatalytic applications of doped halide perovskite QDs/Ni-MOF nanocomposites. Highlights: The Pt 2+ -doped CsPbBr3 QDs/Ni-MOF nanocomposites have first been successfully fabricated. The resultant nanocomposites exhibit excellent photoactivity on H2 production. The enhanced thermal stability and photocatalytic activity of the nanocomposites was discussed.